Input Power Measurement System for Driving Motor in Testing Low-Speed Generator - Ignasius Eko Yuliyanto; Tjendro Tjendro; Bernadeta Wuri Harini; Martanto Martanto (International Journal of Applied Sciences and Smart Technologies, 2023)
Rapid technological advances are affecting the greater use of electrical energy. One of the devices that can generate electrical energy is a generator. Testing the characteristics of the generator required a drive motor to rotate the generator shaft. This research aims to create a three-phase input power measurement system for driving a motor. The method of measuring input power is by measuring the current and voltage of each phase. The power is obtained from the multiplication between current and voltage. The system consists of current sensors, voltage sensors, a signal conditioning circuit, and an Arduino Mega microcontroller for data processing. The system is equipped with a graphical user interface, data storage, and application. The generator input power measurement system has been created and tested. The measurement system has successfully measured the input power of the generator's driving motor, which in real-time is displayed on the trend graph via the graphical user interface on the laptop. The input power measurement data on the three-phase generator and the time data have been successfully stored inside the micro-SD. The average error of the voltage reading is 2% compared to the measurement of the reference voltmeter. The current reading error was 2% compared to the reference meter ampere measurement.